Wild Ornamental Plants of Asteraceae of Karnataka - Sagar, Kavitha; Shivashankar, P. N. (Indian Forester, 2023)
Beauty is the main trait of ornamental plants, hence these ornamental plants are primarily grown for their beauty either for color or aesthetic reasons. Ornamental plants are annual, biennial and perennials and these have magnificent role in creating employability and in developing economy at the local and regional level. The present investigation is about the wild ornamental plants of family Asteraceae of Karnataka with their utility and cultivation methods. Enhancing their values as ornamentals with respect to various ways of utilizing them either through as landscaping, fencing plants, indoor and outdoor pot plants. Their cultivation methods are also briefly discussed. These plants are available and found to be grown in wild. Hence these plants can be explored as potential ornamental plants which not only are important to mankind but also they can be developed as plants with enhanced aesthetic values which directly or indirectly plays role in adding value to the economy of the region where it is grown.